A entrevista jornalística: uma análise do gênero a partir de exemplares publicados no jornal Zero Hora - Borba, Marcelo Silvano (2007)
This study aimed to analyze the genre “journal interview” published by print media. Based on the socio-rhetorical approach to genre analysis, in special the studies of Swales, Bhatia and Bazerman, the nature of the journalist interview was investigated in a corpus of 32 occurrences of the genre published in November 2005 in the newspaper Zero Hora, from Porto Alegre (RS, Brazil). Bonini’s methodological proposal (2004a) for the interrelated study of newspaper genres was also used in this study, as well as Swales' (1990) analysis of rhetorical moves. The research results indicate, among other things, that the organization of the interview text is composed of three rhetorical moves and 17 steps responsible for the realization of nine textual components (such as the title, the lead andthe box). These findings are connected to the results of other studies previously carried out within the Journal Genres Project (Projeto Gêneros do Jornal - PROJOR), under developement at the University of Southern Santa Catarina (Universidade do Sul de Santa Catarina - UNISUL) since 2002.